SUGAR CHAIN-BRANCHED COMPOSITIONAL MODIFICATION INTERFERON GAMMA - TANIGAWA MINEKO; MAKINO TADASHI; FUKUDA KAZUHIRO; MINOWA MARI; BIZEN FUMIO; TAKEUCHI MAKOTO (1999)
PROBLEM TO BE SOLVED: To obtain the subject interferon γ with enzymatic activity maintained at high levels, excellent in medicinal sustainability, and useful as a medicament or the like by culturing specific transformed cells in a medium. SOLUTION: This sugar chain-branched compositional modification interferon γis obtained by transferring an N-acetylglucosaminyl transferase IV gene and/or an N-acetylglucosaminyl transferase V gene into animal host cells such as a CHO strain capable of producing human interferon γ to afford transformed cells, which, in turn, are cultured in a medium under aerobic conditions. By the way, it is preferable that pharmaceutical preparations are manufactured by including the interferon γ as active ingredient.